An overview of scalp dermatoses in a tertiary care institute - Aravamuthan, Ramesh; Vadivelu, Sampath; Arumugam, Shabari; J., Mukesh Mithran (International Journal of Research in Dermatology, 2020)
Background: The scalp is unique among skin areas in humans, with high follicular density and high rate of sebum production which though providing thermal insulation also creates an environment conducive to superficial mycotic infections and parasitic infestations. As there is a paucity of studies on scalp dermatoses in the Indian and Western literature, a clinical study of these scalp dermatoses can unravel the common clinico-epidemiological manifestations in our population. Methods: This is a prospective observational study conducted for a period of 6 months. All the patients reporting to our department were evaluated for entry into the study and patients having scalp lesions were enrolled. A detailed clinical history and a thorough scalp examination were performed. Results: The incidence of scalp dermatoses is more among adolescents and early adulthood with a male to female ratio 1.8:1. 57% of patients had lesions exclusive to scalp. Scalp was the initial site of presentation in 54.6% of cases who had generalized lesions. Itching (n=107; 53.5%) is the commonest presenting complaint. Among the scalp sites, parietal area was involved the most (73%). The most common dermatoses were psoriasis (21.5%) followed by alopecia areata (11.5%). Conclusions: The scalp dermatoses have significant psychological impact affecting the social profile of the patients. To the best of our knowledge, this is the first Indian study on scalp dermatoses involving all age groups which gives a precise clinical insight into scalp dermatoses.